Perspektif Masyarakat terhadap Terjadinya Diabetes Melitus dan Hipertensi di Desa Sembahe Kecamatan Sibolangit Kabupaten Deli Serdang - Rezeki, Rani Hafni Dwi; Putri, Rizmeyni Azhima; Putri, Devi Oktaviani; Latifah, Nur Aini; Agustina, Dewi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Diabetes Mellitus is condition when blood glucose in the body is not controlled due to impaired sensitivity of pancreatic cells to produce the hormone insulin. Hypertension is a common public health problem in developing countries. Hypertension that is not treated immediately has an impact on the emergence of degenerative diseases, such as heart disease (Hypertension Heart Disease), end-stage renal failure (End Stage Renal Disease), and peripheral vascular disease. Risk factors such as heart disease, hypertension, dyslipidemia, Diabetes Mellitus (DM) should be monitored regularly so as not to cause more serious complications. This paper describes the implementation and evaluation of the achievement of minimum service standards and to find out how the characteristics of patients with diabetes are and to find out how the relationship between blood sugar levels and blood pressure of patients with diabetes type mellitus in health sector cases of hypertension and Diabetes Mellitus (DM) in Sembahe Village, Sibolangit District, Deli Serdang Regency. The method used is a qualitative study with a phenomenological method approach, with the focus of the research on clean and healthy living behavior towards the occurrence of hypertension and diabetes mellitus. The results of this study indicate that it is important to know and prevent hypertension and diabetes mellitus from an early age. With seminars and counseling or education regarding hypertension and diabetes mellitus, this has been carried out for 1 month with the assistance of the Field Supervisor, the village midwife of worship and colleagues-his partner. Door to door counseling, healthy gymnastics and health checks have also been carried out once a month to find out how the health condition of the worshipers is.